A cluster of cystic fibrosis mutations in exon 17b of the CFTR gene: a site for rare mutations. Issue 9 (September 1994) - Mercier, B; Lissens, W; Novelli, G; Kalaydjieva, L; de Arce, M; Kapranov, N; Canki Klain, N; Estivill, X; Palacio, A; Cashman, S
Abstract : Intensive screening has improved our understanding of the profile of mutations in the CFTR gene in which more than 400 mutations have been detected to date. In collaboration with several European laboratories we are involved in such analysis. We have identified 14 new mutations in exon 17b of CFTR, having analysed 780 CF chromosomes, and have compared the frequency of mutations in this exon with that of other regions of the CFTR gene. The results obtained indicate an accumulation of mutations, not only in regions encoding the two nucleotide binding folds, but also in those encoding transmembrane domains of the CFTR gene, in particular exon 17b.